أثر تعلیم المرأة وعملها على بیئتها الأسریة والاجتماعیة - العودة، ابتسام بنت عبدالکریم Aloudah, Ibtesam bint Abdulkarim (جامعة عين شمس - كلية البنات للآداب والعلوم والتربية, 2018)
هدف البحث الحالي إلى دراسة أثر تعليم المرأة وعملها على بيئتها الأسرية والاجتماعية. ولقد استخدم البحث الحالي المنهج الوصفي المسحي بهدف وصف الظاهرة لمناسبته لطبيعة موضوع البحث المستهدف. ولقد تكونت عينة البحث من عدد من الطالبات والموظفات بجامعة الملك سعود حيث بلغ حجم عينة البحث (40) طالبة وموظفة. كما تم الاعتماد على استبانة كأداة لجمع البيانات تكونت من 18 عبارة تم تطبيقها على عينة البحث بعد التأكد من صدقها وثباتها. ولقد أثبتت نتائج البحث أن تعلم المرأة وخروجها للعمل له نتائج إيجابية على العلاقة بين المرأة وزوجها من تعاون واحترام وتحمل للمسؤولية بالإضافة إلى التعامل الجيد مع أطفالها وفهم نفسياتهم، كما أن تعليم المرأة وعملها له دور في تنمية القدرة على حل المشكلات الأسرية وتكوين ثقافة أسرية جديدة والشعور بتقدير العائلة وتعزيز العلاقات الاجتماعية.
The current research aimed at investigating the effect of the woman education and work on her social life and family. The current research adopted the descriptive and survey-based method due to its suitability for measuring the target phenomenon and fulfilling the research purpose. The participants of the study were 40 female students and employees at King Saud University. A questionnaire was developed consisting of 18 items and was administered to the research participants after assuring its validity and reliability. The results of the research revealed that woman education and work have positive effects on the relationship between the woman and her husband as education and work help the woman to cooperate, respect and hold the responsibility of the family. Furthermore, education and work help the woman to deal in a good way with her children and understand their needs and they enable her to solve the family problems, form good family culture, realize her family respect and support her social relationships.
Keywords: التعلیم -- العمل -- المرأة العاملة -- البیئة الأسریة -- البیئة الاجتماعیة -- السعودية